Gender and Jewishness: a Greimassian analysis of Susanna - D. M. Kanonge (Acta Theologica)
This article investigates the possible gender agenda of Susanna. Gender is one of the most debated issues in the study of the story. A frequently asked question is: “does Susanna reinforce or undermine patriarchy?” Most scholars, mainly feminists, are pessimistic and suspicious about the subversive programme of Susanna. This study addresses the above concern using the Greimassian approach to narratives, as refined by Everaert-Desmedt. The approach comprises three levels of analysis: the figurative, the narrative and the thematic. Results from preliminary analysis appear to highlight “Jewishness” as the main concern here. True Jewishness seems to depend exclusively on the commitment to the Law, regardless of gender. A woman such as Susanna, committed to the Law even to the cost of her life, is a true Jew (??????? ??????). Men like the elders, opposing the Law, are corrupt and corrupting strangers (?????? ??????). Accordingly, Susanna undermines rather than reinforces patriarchy.